Climate change liability : transnational law and practice - Lord, Richard , 1959- (Cambridge University Press, 2012)
"As frustration mounts in some quarters at the perceived inadequacy or speed of international action on climate change, and as the likelihood of significant impacts grows, the focus is increasingly turning to liability for climate change damage. Actual or potential climate change liability implicates a growing range of actors, including governments, industry, businesses, non-governmental organisations, individuals and legal practitioners. Climate Change Liability provides an objective, rigorous and accessible overview of the existing law and the direction it might take in seventeen developed and developing countries and the European Union. In some jurisdictions, the applicable law is less developed and less the subject of current debate. In others, actions for various kinds of climate change liability have already been brought, including high profile cases such as Massachusetts v. EPA in the United States. Each chapter explores the potential for and barriers to climate change liability in private and public law"-- Provided by publisher.